On Face Index of Silicon Carbides - Xiujun Zhang; Ali Raza; Asfand Fahad; Muhammad Kamran Jamil; Muhammad Anwar Chaudhry; Zahid Iqbal (Discrete Dynamics in Nature and Society)
Several graph invariants have been defined and studied, which present applications in nanochemistry, computer networks, and other areas of science. One vastly studied class of the graph invariants is the class of the topological indices, which helps in the studies of chemical, biological, and physical properties of a chemical structure. One recently introduced graph invariant is the face index, which can assist in predicting the energy and the boiling points of the certain chemical structures. In this paper, we drive the analytical closed formulas of face index of silicon carbides Si2C3−Ia,b, Si2C3−IIa,b, Si2C3−IIIa,b, and SiC3−IIIa,b.